ENVIRONMENTALLY FRIENDLY AND ECONOMICALLY SUSTAINABLE LOCAL PEATLAND CULTIVATION STRATEGIES - Muhammad Noor Fazri Edison Edison; Suprayitno; Niwayan Sukraini (Sociae Polites, 2020)
Kalampangan subdistrict is located in the north part of Palangka Raya Town in Central Kalimantan. Kalampangan was built on approximately four-meter-deep peat. At first, the land was not productive because it was very acidic. However, after many years of hard work, Kalampangan has been successful in providing vegetables, fruits, and meat for Palangka Raya and its surrounding regions. The local farmers in Kalampangan cultivate the deep peatland in an environmentally friendly way, i.e., by adding manure and ash of weeds. As a result of this local wisdom-based practice, the soil becomes fertile and productive for horticultural products, and subsequently, the plant residue is utilized for animal feed. This integrated horticulture and livestock farming have made Kalampangan the biggest produce and livestock supplier for Palangka Raya and the surrounding regions. This paper aims at describing the detailed strategies of this integration by collecting data through interviews with the local administration and farmers. Keywords: Kalampangan, peatland, horticulture, livestock farming, productive